2022
DOI: 10.1139/er-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Shorebirds ingest plastics too: what we know, what we do not know, and what we should do next

Abstract: Concerns about the impact of plastics pollution on the environment have been growing since the 1970s. Marine debris has reportedly entangled and/or been ingested by 914 marine species ranging from microinvertebrates to large marine mammals. Shorebirds could have a high potential to be exposed to and ingest plastics pollution, as many species migrate long distances and periodically concentrate around shorelines, coastal areas, and estuaries that can have elevated levels of plastics pollution. Currently, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Marine birds are also at risk from the ingestion of plastics. Red phalaropes, as surface feeders, appear to be especially vulnerable to plastic ingestion (Moser & Lee 1992, Drever et al 2018, Baak et al 2020, Flemming et al 2022, perhaps due to the species' preferential selection of oceanographic features that concentrate plastics such as convergences and eddies (Moore et al 2001). For example, in our study, we showed that red phalaropes often stopped within the North Pacific Current, which is at the northern boundary of the plastic-laden 'Great Pacific Garbage Patch' (Lebreton et al 2018).…”
Section: Conservation Implicationsmentioning
confidence: 53%
See 1 more Smart Citation
“…Marine birds are also at risk from the ingestion of plastics. Red phalaropes, as surface feeders, appear to be especially vulnerable to plastic ingestion (Moser & Lee 1992, Drever et al 2018, Baak et al 2020, Flemming et al 2022, perhaps due to the species' preferential selection of oceanographic features that concentrate plastics such as convergences and eddies (Moore et al 2001). For example, in our study, we showed that red phalaropes often stopped within the North Pacific Current, which is at the northern boundary of the plastic-laden 'Great Pacific Garbage Patch' (Lebreton et al 2018).…”
Section: Conservation Implicationsmentioning
confidence: 53%
“…In addition to climatic changes, seabirds also face other anthropogenic threats including the ingestion of plastics, especially microplastics that float on the surface (Moser & Lee 1992, Drever et al 2018, Baak et al 2020, Flemming et al 2022, increased vessel traffic that can result in disturbance and collisions (CAFF 2017), disorientation and fatal attraction to lights produced by ocean vessels and developments (Merkel 2010, Gjerdrum et al 2021, the release of contaminants from marine vessels and oil and gas developments and their associated activities (Tyler et al 1993, Wahl et al 1993, O'Hara & Morandin 2010, and disturbance, displacement, and collisions with offshore wind farms (Garthe & Hüppop 2004, Stienen et al 2007, Furness et al 2013, Dierschke et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Another species also affected by plastic ingestion was Hornby's storm petrel (H. hornbyi), represented by one individual who had regurgitated a piece of a plastic bag. In the present study, ingestion represented a low percentage of the interactions (3%); this could be due to our methodological limitation, even though plastic ingestion by birds has been frequently reported by scientists worldwide (Battisti et al 2019, Rossi et al 2019, Flemming et al 2022.…”
Section: Ingestionmentioning
confidence: 57%
“…Shorebirds face threats across their geographical range, often associated with climatic and other anthropogenic changes, including loss of breeding habitats, threats on migratory stopover sites and increased predation rates (Kubelka et al 2018, Von Holle et al 2019, Jackson et al 2021, Flemming et al 2022, Wang et al 2022. The capacity of shorebird populations to tolerate and adapt to these challenges is likely to be modulated by sex role variation, although there is no consensus as to the direction of such an effect (Legendre et al 1999, Doherty et al 2003, Morrow & Pitcher 2003.…”
Section: Sex Roles Population Resilience and Conservationmentioning
confidence: 99%